Green copper oxide nanoparticles for lead, nickel, and cadmium removal from contaminated water - Alaa El Din Mahmoud (Nature Portfolio, 2021)
Abstract Environmentally friendly copper oxide nanoparticles (CuO NPs) were prepared with a green synthesis route without using hazardous chemicals. Hence, the extracts of mint leaves and orange peels were utilized as reducing agents to synthesize CuO NPs-1 and CuO NPs-2, respectively. The synthesized CuO NPs nanoparticles were characterized using scanning electron microscopy (SEM), Energy Dispersive X-ray Analysis (EDX), BET surface area, Ultraviolet–Visible spectroscopy (UV–Vis), and Fourier Transform Infrared Spectroscopy (FT-IR). Various parameters of batch experiments were considered for the removal of Pb(II), Ni(II), and Cd(II) using the CuO NPs such as nanosorbent dose, contact time, pH, and initial metal concentration. The maximum uptake capacity (qm) of both CuO NPs-1 and CuO NPs-2 followed the order of Pb(II) > Ni(II) > Cd(II). The optimum qm of CuO NPs were 88.80, 54.90, and 15.60 mg g−1 for Pb(II), Ni(II), and Cd(II), respectively and occurred at sorbent dose of 0.33 g L−1 and pH of 6. Furthermore, isotherm and kinetic models were applied to fit the experimental data. Freundlich models (R2 > 0.97) and pseudo-second-order model (R2 > 0.96) were fitted well to the experimental data and the equilibrium of metal adsorption occurred within 60 min.